Dakwah pada Masyarakat Terasing Upaya Dewan Dakwah Islam Indonesia (DDII) terhadap Suku Akit SondeRiau - Dadang Budiman (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2018)
This study aims to determine the concept and implementation of the da'wah of the Indonesian Islamic Da'wah Council (DDII) in the isolated community of the Sonde Islands Riau Islands tribe. This research uses descriptive-qualitative method by collecting data through in-depth interviews with a number of da'wah figures in DDII, and is equipped with various physical evidence from various documents so as to achieve a level of validity that is in accordance with scientific standards. Based on the results of the study it was found that: First, Da'wah for isolated communities of the Akit Sonde Tribe was focused on fulfilling their spiritual needs. In accordance with the ideals of DDII preaching should be carried out continuously to various regions to all humanity. Secondly, the implementation of da'wah was demonstrated by the steps DDII sent preachers on an ongoing basis to the Sonde tribe community. Third, DDII da'wah efforts were also taken by establishing educational institutions, mosques, Islamic centers, waqf jama'ah management, guidance and services for Hajj and others. DDII turned out to have done for isolated communities through the act of real da'wah in the midst of their lives.Keywords: Da'wah; Isolated Society; DDII.ABSTRAKPenelitian ini bertujuan untuk mengetahui konsep dan implementasi dakwah Dewan Dakwah Islamiyyah Indonesia (DDII) pada masyarakat terasing suku Akit Sonde Kepulauan Riau. Penelitian ini menggunakan metode deskriptif-kualitatif dengan pengumpulan datanya melalui wawancara mendalam terhadap sejumlah tokoh dakwah di DDII, dan dilengkapi dengan berbagai bukti fisik dari berbagai dokumen sehingga mencapai tingkat keabsahan yang sesuai dengan standar ilmiah. Berdasarkan hasil penelitian ditemukan bahwa: Pertama, Dakwah bagi masyarakat terasing Suku Akit Sonde difokuskan pada pemenuhan kebutuhan spiritual mereka. Sesuai dengan cita-cita DDII dakwah hendaknya dilakukan terus menerus ke berbagai wilayah kepada seluruh umat manusia. Kedua, implementasi dakwah ditunjukkan dengan langkah DDII  mengirimkan para pendakwah secara berkesinambungan kepada masyarakat suku Sonde. Ketiga, upaya dakwah DDII juga ditempuh dengan mendirikan lembaga pendidikan, mesjid, islamic centre, pengelolaan wakaf jama’ah, pembinaan dan pelayanan haji dan lain-lain. DDII ternyata telah berbuat untuk masyarakat terasing melalui aksi dakwah nyata di tengah-tengah kehidupan mereka.